2021
DOI: 10.47059/alinteri/v36i1/ajas21011
|View full text |Cite
|
Sign up to set email alerts
|

Shading Treatments Improved Plant Growth and Physiological Responses of Sweet Cherry Plants Subjected to Salt Stress

Abstract: The responses of sweet cherry plant to salt stress and shading treatments were investigated in the study. The study was performed in a greenhouse with 1-year-old 0900 Ziraat sweet cherry cultivar grafted onto MaxMa 14 grown in 10 L pots. About 2 months after planting, salinity and shading treatments were initiated. Three levels of shading (40, 60 and 80%) were employed. 35 mM NaCl (sodium chloride) was used to expose plants to moderate salt stress. The plants were stressed during four months. Many morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Furthermore, Fan et al (2019) described that shading plants contain more chlorophyll for efficient light capture. Similar results to the present study were observed by Aras et al (2021) in the sweet cherry tomato crop grown in a protected environment and under salt stress.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Fan et al (2019) described that shading plants contain more chlorophyll for efficient light capture. Similar results to the present study were observed by Aras et al (2021) in the sweet cherry tomato crop grown in a protected environment and under salt stress.…”
Section: Resultssupporting
confidence: 92%
“…Nojosa Lessa et al (2022), state that plants exposed to sunlight under salt stress show higher rates of uptake and translocation of potentially toxic ions when compared to shaded plants. In a study evaluating the responses of sweet cherry to salt stress under different shading, Aras et al (2021), found that the stomatal conductance of the plants reduced when grown under salt stress in a non-shaded environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation